222Long-term mortality after early famine exposure: findings from the China Kadoorie Biobank. (2nd September 2021) - Meng, Ruogu; Yu, Canqing; Guo, Yu; Bian, Zheng; Yang, Ling; Chen, Yiping; Du, Huaidong; Chen, Junshi; Chen, Zhengming; Lv, Jun; Li, Liming
Abstract: Background: Previous studies suggested that increased risks of chronic diseases in China might be attributable to early experience of the Chinese Great Famine during last century, but the reliable evidence for adult mortality was rare. This study is to investigate the association of early famine exposure with death risks in the middle age. Methods: A number of 94 051 participants from China Kadoorie Biobank were categorized as non-famine births (born between 10/1/1956 and 9/30/1958, and 10/1/1962 and 9/30/1964) and famine births (born between 10/1/1959 and 9/30/1961). The outcomes were total and cause specific mortality. Cox regression was used to estimate hazard ratio (HR) for famine exposure. Results: During a median 10.2 years of follow-up, we documented 2802 total deaths in all participants. Prenatal famine exposure was only associated with the risks of ischemic heart disease (IHD) mortality in adulthood (310 deaths, HR [95% CI]: 1.34 [1.02, 1.75]), compared with non-famine births. We also observed the association of famine with total mortality (HR [95% CI]: 1.42 [1.12, 1.78]) in daily alcohol drinkers, but not in non-daily drinkers (P for interaction: 0.025). Conclusions: This study indicated that early famine exposure was associated with an increased death risk of heart disease and such risk may be modified by adult alcohol consumption. Key messages: Early Chinese famine experience might impact adult IHD deaths. Coexistence of early famine experience and adult alcohol consumption was associated with higher risks of total mortality.